Pengaruh Free Cash Flow, Profitabilitas, Kualitas Audit, Leverage, Kebijakan Dividen terhadap Likuiditas Pada Perusahaan Terdaftar di Jakarta Islamic Index - Yohana Yohana; Ruth Marito Lumban Gaol; Ghina Kemala Dewi; Nawang Kalbuana; Alwazir Abdusshomad (Jurnal Ilmiah Ekonomi Islam, 2021)
This research aims to test the effect of free cash flow, profitability, audit quality, leverage and dividend policy on liquidity. In this study, the companies studied were companies listed on the Jakarta Islamic Index and listed on the Indonesia Stock Exchange for the period 2016 to 2020. The study used secondary data with a quantitative approach. The number of companies studied by 17 companies in the space of 5 years. The research method used is multiple linear regression analysis using spss 25 application with data analysis techniques used namely normality test, heterocedasticity test, multicollinearity test, multicolutarity test, and multiple linear regression analysis. The results of this study showed that free cash flow had no effect on liquidity, profitability had no effect on liquidity, audit quality had an effect on liquidity, leverage had no effect on liquidity and leverage had no effect on dividend policy.